Superconducting states in strongly correlated systems with nonstandard quasiparticles and real space pairing: an unconventional Fermi-liquid limit - Spałek, J. (Condensed Matter Physics, 2010)
We use the concept of generalized (almost localized) Fermi Liquid composed of nonstandard quasiparticles with spin-dependence effective masses and the effective field induced by electron correlations. This Fermi liquid is obtained within the so-called statistically-consistent Gutzwiller approximation (SGA) proposed recently [cf. J. Je¸drak et al., arXiv: 1008.0021] and describes electronic states of the correlated quantum liquid. Particular emphasis is put on real space pairing driven by the electronic correlations, the Fulde-Ferrell state of the heavy-fermion liquid, and the d-wave superconducting state of high temperature cuprate superconductors in the overdoped limit. The appropriate phase diagrams are discussed showing in particular the limits of stability of the Bardeen-Cooper-Schrieffer (BCS) type of state.